Combined postharvest X-ray and cold quarantine treatments against the Mediterranean fruit fly in "Clemenules" mandarins - Palou, L.=700 1 Del Rio, M.A.; Marcilla, A.; Alonso, M.; Jacas, J.A.
Es, En)
Ilus., 40 ref.
Keywords: CITRUS RETICULATA; ANALISIS ORGANOLEPTICO; CALIDAD; FRUTAS; CERATITIS CAPITATA; IRRADIACION POR RAYOS; CUARENTENA; ESPAÑA